PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK WARDAH DI GARUT KOTA - Nazwa Hidayat, Erika; Ramayani Yusuf (Jurnal Manajemen dan Pemasaran, 2024)
PT Paragon Technology and Innovation, the largest cosmetics manufacturing company in Indonesia, makes Wardah, one of the beauty brands that was first launched to the public in 1995. In the fourth year, PT Paragon launched Wardah products. Wardah succeeded in obtaining Halal certification from LPOM MUI, making it a pioneer of Halal beauty product brands in Indonesia. The researcher's aim in conducting this research is to find out whether there is an influence between the "Brand Image" variable and the "Purchase Decision" variable on Warda products, especially in the Garut City area. The type of research used is a quantitative method with a sample of 100 respondents as representatives of the population/consumers who use Wardha products in the city of Garut. Data was obtained from a questionnaire and processed using the IBM SPSS Statistics 20 analysis tool and a simple linear regression analysis test. The results of the analysis show that the variable Brand Image (X) has a positive and significant influence on the variable Purchase Decision (Y) for Wardha products in the Garut City Area.